On the Cayley-Hamilton property in abelian groups - Robert R. Militello (International Journal of Mathematics and Mathematical Sciences)
In this paper, the work of Casacuberta and Hilton on the class of abelian fg-like groups is extended. These groups share much in common with the class of finitely generated abelian groups.